Effect of logging operations on soil carbon storage of a tropical peat swamp forest in Sarawak, Malaysia - Satrio, Anton Eko (2010)
There is little published data on the effect of logging operation on soil carbon storage of peat swamp forests. Furthermore, there is still lack of study that compares the damage level caused by “kuda-kuda” (sledge) skidding system and excavator skidding system in peat swamp forests. Thus, it is important to investigate the severity of degradation of peat swamp forest caused by logging operation in terms of its function as carbon storage. There are four major components of the logging operation, but the special concern remains the skidding component because it mainly interacts with the ground while extracting the trees through its damaging impact on the soil. The study area is located in an area bound by Batang Lebaan and Batang Igan River, adjacent to Sibu town. This peat swamp forest is Alan Batu forest type which is generally found on a more stressful environment of the peat swamp. In this study, it was assumed that conditions of the study site before the introduction of skidding system were in their natural state, and the changes measured are mainly caused by the skidding system. Therefore, the first part of this study was to determine the soil carbon storage of a tropical peat swamp forest in their natural state. Variables obtained such as bulk density, soil pH, SOM, total carbon, total nitrogen, and C/N ratio was evaluated against their typical standard range that reported on earlier published references. The correlation between aforementioned chemical properties, humic acid (HA), unstable carbon, and stable carbon was examined. This tropical peat swamp forest portrays its specific natural state such as rich in SOM but had extreme acidic environment, thereby inhibiting decomposition of organic matter. It also had large amounts of total carbon, low total nitrogen, and high C/N ratio. The soil carbon storage in this tropical peat swamp forest relates to unstable carbon. A high value of soil carbon storage (± 61.49% of unstable carbon) in this peat swamp forest soil suggests that this natural tropical peat swamp forest plays an important role as a sink rather than a source of carbon. The second part of the study was to determine whether rainfall affects soil carbon storage of a tropical peat swamp forest and to determine the correlations which exist between variables (pH, SOM, total carbon, total nitrogen, total phosphorus, C/N ratio, C/P ratio, HA, unstable carbon, and stable carbon) that cause changes in soil carbon storage. The aforementioned variables of paired plots under two different rainfall gradients were compared and their correlations were examined. Stable carbon positively correlated with unstable carbon under higher rainfall. However, stable carbon had no association with unstable carbon under lower rainfall. The percentage of stable carbon of unstable carbon was 42.93% under lower rainfall, while that of higher rainfall was 62.69% suggesting that this natural tropical peat swamp forest plays an important role as a sink rather than a source of carbon under higher rainfall but inversely under lower rainfall. The third part of the study was to determine whether skidding operations affects soil carbon storage of a tropical peat swamp forest. Bulk density and variables such as soil pH, SOM, total carbon, total nitrogen, total phosphorus, C/N ratio, C/P ratio, HA, unstable carbon, and stable carbon of independent plots under the two systems, “kuda-kuda” (sledge) and excavator skidding systems were compared and the correlations between variables were examined. It showed that the use of skidding systems on tropical peat swamp forest alters their carbon storage particularly unstable carbon by altering their decomposition rates. The fourth part of the study was to determine whether logging operation affect soil carbon storage of a tropical peat swamp forest. Variables such as soil pH, SOM, total carbon, total nitrogen, total phosphorus, C/N ratio, C/P ratio, HA, unstable carbon, and stable carbon under the two treatments (before and after logging) were compared and the correlations between these variables were examined. Result indicates that after the peat swamp forest is logged, humification maintained but the process slows and poor, hence unstable carbon decomposes faster instead of being preserved as stable carbon. Logging operations in this peat swamp forest does not alter their amount of soil carbon storage (stable carbon) due to the carbon in humic acid is quite stable within one year.